WPŁYW MEDIÓW NA KREOWANIE WIZERUNKU STAROŚCI W REKLAMIE TELEWIZYJNEJ – BADANIE PILOTAŻOWE - Kowalewska, Kinga (Scripta Neophilologica Posnaniensia, 2019)
The purpose of the article is to find the answer to the questions whether television commercials have an impact on creating the image of the elderly and what image of old age and lifestyle of the elderly is built on the basis of television ads. Studies have confirmed the hypothesis and have shown that the media through the content presented in TV commercials have a real impact on the shape of the image of the elderly population. The results allow the media to be seen as strong and efficient tools in the process of creating the image as such, also of other populations or individuals. The qualitative results have shown that the image of old age is seen mainly as positive and neutral, whereas their lifestyle is perceived as real, idealized and attractive.